Website Implementation with the Monte Carlo Method as a Media for Predicting Sales of Cashier Applications - Elfina Novalia; Jufriadif Na'am; Gunadi Widi Nurcahyo; Apriade Voutama (SYSTEMATICS, 2020)
System implementation is a testing process to make it easier for users to carry out the calculation process or process data. by testing it can be concluded whether or not a system is designed. One of them is the implementation of a website-based system to predict sales of cashier applications by applying the Monte Carlo method. Increasing sales of cashier applications currently make developer companies have to prepare quality and feasible software or applications as needed. To maintain an increase in profit, it is necessary to prepare and manage the right human resources. One of them is to simulate to predict future sales of applications by utilizing the Monte Carlo method which has been translated and implemented into a website. From the algorithm, a system implementation is carried out where the calculation process that has been built using Monte Carlo is translated into a website. Website design tools use UML with the PHP programming language and MySQL database. The website is tested and implemented whether the system that has been built is working properly and in accordance with the calculations made previously so that this system can facilitate the simulation process easily and effectively.